2017
DOI: 10.1177/1363460717716581
|View full text |Cite
|
Sign up to set email alerts
|

On sex in fieldwork: Notes on the methodology involved in the ethnographic study of anonymous sex

Abstract: This article addresses the use of sexual relations with research informants in fieldwork for the purpose of gathering information. The analysis is based on the research that the author himself carried out between 2009 and 2014 on anonymous sexual encounters between men in public places in Catalonia. The article aims to demonstrate that sexual interaction with informants – notwithstanding appeals to scientific objectivity and professional ethics – can be a useful tool for gaining a better understanding of socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…[77][78][79] Following the MMPI and talking with homosexual and heterosexual participants, it manifested their childhood experiments have indirectly influenced behavior and personality traits as having a homosexual or bisexual orientation in adulthood. [80][81][82] Being heterosexual, homosexual, or bisexual is not something that a person can indisputably choose or choose to change because some other ecological backgrounds such as ethnic, biological, genetic, social, and economic factors can determine sexual orientation as a part of someone's nature. [83][84][85][86][87] Moreover, Herek et al have reported that most respondents experienced little or no choice about their sexual orientation.…”
Section: Discussionmentioning
confidence: 99%
“…[77][78][79] Following the MMPI and talking with homosexual and heterosexual participants, it manifested their childhood experiments have indirectly influenced behavior and personality traits as having a homosexual or bisexual orientation in adulthood. [80][81][82] Being heterosexual, homosexual, or bisexual is not something that a person can indisputably choose or choose to change because some other ecological backgrounds such as ethnic, biological, genetic, social, and economic factors can determine sexual orientation as a part of someone's nature. [83][84][85][86][87] Moreover, Herek et al have reported that most respondents experienced little or no choice about their sexual orientation.…”
Section: Discussionmentioning
confidence: 99%
“…Las personas que interaccionan y comunican en el marco de una investigación, lo hacen en calidad de agentes encarnadas, corporizadas en contextos concretos, localizados y parciales (Esteban, 2009;Langarita, 2019). A partir de las experiencias reflexivas entre las personas que investigan, y especialmente las mujeres que ejercen trabajo sexual, así como otras personas informantes, intentaremos conectar lo material con lo discursivo (Feely, 2019), es decir, cómo los cuerpos y sus afectos-emociones constituyen parte de los discursos sociales y viceversa.…”
Section: Introductionunclassified
“…This leads to the third contribution of the paper; that is, bringing back sex itself into the core of the analysis within geographies of sexualities, notably one of the practices that has created most controversial public debates in recent years in many countries around the globe. Geographies of sexualities have increasingly become a legitimate field of studies, but despite its popularity, the engagement with sexual practices has remained limited (Bell, 2007; Binnie, 1997; Brown et al, 2011; Brown & Di Feliciantonio, 2022; for some exceptions see Bain & Nash, 2006; Bonner‐Thompson, 2017, 2021; Brown, 2008a; Di Feliciantonio, 2019; Gurney, 2000; Langarita, 2019; Misgav & Johnston, 2014; Sanders‐McDonagh, 2017), its main focus being on identities (Binnie & Valentine, 1999; Brown, 2012; Browne et al, 2007; Johnston, 2016). Conceptualising spaces and subjectivities as always emerging and provisional (Jones, 2009), the relational understanding of place adopted in the paper allows us to explore what bodies can do in the ‘messiness’ of sexual desire (Brown, 2008a; Lim, 2007), reaffirming the spatial character of sexual practices as they are ‘assembled through a myriad of materials (human and non‐human, organic and inorganic) and expressive forces (moods, emotions, intensities and affects)’ (Bonner‐Thompson, 2021, p. 452).…”
Section: Introductionmentioning
confidence: 99%